The politics of regional identity : meddling with the Mediterranean - Pace, Michelle, 1970- (Routledge, 2006)
Focusing on the politics of representation and constructions of identity, the author analyses the impact of European regionalism on the Mediterranean.
Keywords: Regionalism.; Regionalism -- Mediterranean Region.; Regionalism -- European Union countries.; Mediterranean Region -- Foreign relations -- European Union countries.; European Union countries -- Foreign relations -- Mediterranean Region.; Geopolitics -- Mediterranean Region.; Geopolitics -- European Union countries.; Régionalisme.; Régionalisme -- Pays de l'Union européenne.; Méditerranée, Région de la -- Relations extérieures -- Pays de l'Union européenne.; Géopolitique -- Pays de l'Union européenne.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Geopolitics; Diplomatic relations; Regionalism; European Union countries; Mediterranean Region